Novel double-track sweat soldering process for geomembrane
By flattening and roughening the bottom surface of the warehouse, and using the dual-track automatic hot melt welding process, the problem of geomembrane leakage is solved, the adhesion and anti-seepage performance are improved, the service life is extended, and the engineering anti-seepage requirements are met .
Patent Information
- Application Number
- CN202411431496.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-27
AI Technical Summary
During the construction process, the concentration stress caused by voids or bubbles increases, resulting in leakage problems, which cannot meet the construction requirements at the bottom of the warehouse.
The new geomembrane adopts the dual-track hot melt welding process, and the surface of the bottom of the warehouse is flattened and roughened, ensuring the firm attachment of the geomembrane, and welding is performed through the dual-track automatic hot melt welding machine, and the overlap width and welding temperature are adjusted. Ensure stability and anti-seepage performance between membrane blocks.
It improves the adhesion and anti-seepage performance of geomembrane, extends the service life, enhances the stability and durability of the engineering structure, and meets the engineering anti-seepage requirements.
Smart Images

Figure BDA0005083794530000101
Abstract
Description
Technical Field
[0001] The present application relates to a novel double-track hot-melt welding process for geomembrane, belonging to the technical field of geomembrane construction. Background Art
[0002] Anti-seepage construction in reservoir areas is a key link in the fields of water conservancy projects, environmental protection projects, construction projects, etc. Its purpose is to prevent water, chemicals or pollutants from penetrating into the soil, thereby protecting the safety of groundwater resources and the surrounding environment. In this field, geomembrane construction technology has become an important and indispensable engineering practice due to its outstanding anti-seepage effect, long-term stability and engineering economy.
[0003] In actual projects, due to construction, geology, materials and other reasons, gaps or bubbles often appear between the geomembrane and the reservoir bottom. The concentrated stress generated in these areas gradually increases with time. When encountering water erosion, soil settlement and other conditions, the geomembrane will be damaged or fail, resulting in leakage problems, and therefore cannot meet the construction requirements of the reservoir bottom. Summary of the invention
[0004] In order to solve the above problems, a double-track hot-melt welding process for a new type of geomembrane is provided. The frosted surface of the new geomembrane can fit tightly with the rough surface of the reservoir bottom, and relative sliding is not likely to occur between the two, thereby extending the service life of the geomembrane and meeting the engineering anti-seepage requirements.
[0005] The present invention adopts the following technical solutions:
[0006] A new type of double-track hot-melt welding process for geomembrane, including:
[0007] (1) The bottom surface of the silo is flattened to ensure that there are no impurities within a vertical depth of 20-25 mm, and then the bottom surface is roughened to ensure that the depth of the roughness of the bottom surface is 3-5 mm;
[0008] (2) According to the reservoir bottom conditions, the geomembrane is cut into appropriate sizes and numbered for record. The exposed edges of the geomembrane are covered with sand bags;
[0009] (3) The TPO geomembrane, the new geomembrane and the HDPE geomembrane are overlapped in sequence and welded by a double-track automatic hot-melt welding machine to fuse the edges of the adjacent geomembranes;
[0010] (4) Mark the defects detected on the geomembrane and arrange for repairs until the retest is qualified;
[0011] The novel geomembrane comprises a substrate layer and an anti-slip layer coated on the lower surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-slip layer is 1:(0.1-0.3).
[0012] Optionally, in step (3), the welding temperature is 400-450° C. and the welding speed is 2-2.5 m / min.
[0013] Optionally, in step (3), the overlap width is 8-12 cm.
[0014] Optionally, the thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is (1-2):1:(1-1.8).
[0015] Optionally, the novel geomembrane is prepared by the following method:
[0016] a. By weight, 30-45 parts of high-density polyethylene, 25-32 parts of low-density polyethylene, 20-27 parts of linear low-density polyethylene, 15-25 parts of polyethylene, 12-18 parts of ethylene-octene copolymer, 15-20 parts of polyetheretherketone, 10-16 parts of polycarbonate, 8-13 parts of modified polyester fiber, 7-12 parts of phenyl p-isopropyl salicylate, 6-11 parts of boron nitride and 1-3 parts of antioxidant are placed in a twin-screw extruder, the main engine speed is 50-60rpm, and the extrusion die is extruded at 170-180°C and then calendered to obtain a substrate layer;
[0017] b. Dissolve 6-15 parts of thiophenyl-parathiocyanoacetone and 5-10 parts of isopropylthioxanthone in 10-25 parts of hexanediol diacrylate and 8-20 parts of tripropylene glycol diacrylate, and stir at 40-50° C. for 20-40 minutes, then add 42-70 parts of aliphatic polyurethane acrylate, 15-30 parts of hyperbranched polyester acrylate, 15-30 parts of polypropylene frosting powder, 3-7 parts of silicone polyether acrylate and 2-5 parts of fluorine silicon compound, continue stirring for 20-40 minutes, and after standing and stabilizing, obtain an anti-slip coating;
[0018] c. Apply the anti-skid coating on the lower surface of the substrate layer, pre-bake at 60-70°C for 30-50s, and then mature at 40-50°C for 12-24h to form an anti-skid layer and obtain a new geomembrane.
[0019] Optionally, in step a, the antioxidant is selected from at least one of antioxidant 1076, antioxidant 619, and antioxidant 703.
[0020] Optionally, in step a, the method for preparing the modified polyester fiber comprises the following steps:
[0021] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0022] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 1-3 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0023] S3. Stir and mix silane coupling agent and ethanol in a volume ratio of 1:(400-600) at 40-60°C for 1-3h, then add FeCl3 to disperse evenly, then add the initially modified polyester fiber and soak for 1-3h, take out, wash with water, and dry to obtain the modified polyester fiber.
[0024] Optionally, the silane coupling agent is selected from at least one of KH550, KH560, and KH570.
[0025] Optionally, in step S3, the weight of the silane coupling agent is 8-12% of the initially modified polyester fiber.
[0026] Optionally, in step (1), the roughening treatment of the reservoir bottom surface includes one or more of chiseling, grinding, high-pressure jetting, and milling.
[0027] In this application, "TPO" refers to 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0028] "HDPE" refers to high-density polyethylene.
[0029] The beneficial effects of this application include but are not limited to:
[0030] 1. The double-track hot-melt welding process of the new geomembrane of the present application, by flattening and roughening the surface of the reservoir bottom, ensures that there are no uneven or sharp objects in the construction area to avoid damage to the geomembrane, and can ensure that the geomembrane is firmly attached to the substrate to provide better adhesion, so that the performance of the geomembrane remains stable during use; according to the soil type, thickness, particle distribution and groundwater level of the reservoir bottom, appropriate geomembrane materials are selected during construction to ensure that they can cope with geological conditions; the overlap method between the membrane blocks of the present application can effectively disperse stress, prevent damage caused by stress concentration, and improve the stability and durability of the engineering structure; by inspecting and protecting the geomembrane after welding, the integrity and anti-seepage performance of the geomembrane are ensured, which helps to extend the service life of the geomembrane.
[0031] 2. The double-track hot-melt welding process of the new geomembrane of the present application is carried out by a double-track automatic hot-melt welding machine, which has a higher degree of automation and thus helps to improve construction efficiency; by setting an anti-slip layer, it helps the geomembrane to better adhere to the bottom of the reservoir, preventing it from slipping or falling off during use, reducing the risk of damage caused by local stress concentration, and thus improving the anti-seepage effect; the welding temperature, welding time and overlap width between adjacent membrane blocks are adjusted according to the type and thickness of the geomembrane to ensure the welding quality.
[0032] 3. The double-track hot-melt welding process of the novel geomembrane of the present application, by selecting appropriate raw materials, proportions and processes, makes the novel geomembrane have excellent anti-seepage effect, mechanical strength and durability, and is suitable for various complex geological and climatic conditions; wherein, by adding aliphatic polyurethane acrylate and hyperbranched polyester acrylate, the obtained anti-slip layer coating can have low viscosity, fast curing speed, excellent adhesion, flexibility and wear resistance, and hexanediol diacrylate and tripropylene glycol diacrylate can well dilute the viscosity of the system and improve the coating's adhesion to the substrate The adhesion of the ink is improved, the flexibility and wear resistance of the system are improved, the anti-slip layer coating prepared with thiophenyl-parathiocyanoacetone and isopropylthioxanthone has an excellent curing speed, which maximizes the double bond conversion rate. The polypropylene frosting powder has stable performance and is easily dispersed in the prepared anti-slip layer coating. It has good frosting effect, high roughness and low smoothness. The addition of siloxane polyether acrylate and fluorosilicone compounds can effectively improve the adhesion and wear resistance of the ink. The combined effect of various raw materials makes the prepared anti-slip layer coating have excellent overall performance and meets the coating requirements on the substrate layer.
[0033] 4. The double-track hot-melt welding process of the novel geomembrane of the present application uses a silane coupling agent and dopamine to synergistically modify the polyester fiber. On the one hand, the hydroxyl group of the silane coupling agent can react with the hydroxyl group and amino group of polydopamine, and the active group of the silane coupling agent can react with the active group of polydopamine and Fe 3+ The formation of complexes allows the fiber surface to be coated with more silane coupling agents. The hydroxyl groups exposed on the fiber surface can chemically bond with the matrix, and the amino-terminal carbon chain can be entangled with the matrix. On the other hand, more silane coupling agents attached can increase the roughness of the fiber surface, which is beneficial to increase the action sites between the fiber and the matrix and enhance the degree of fit between the two without affecting the internal structure of the fiber. Therefore, the interfacial bonding strength between the fiber and the matrix is further improved, so that the fiber can effectively transfer the load, and the interface with the matrix can withstand a larger load. When debonding occurs, there is still a matrix attached to the fiber surface, thereby improving the mechanical properties of the new geomembrane. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0036] Example 1
[0037] A new type of double-track hot-melt welding process for geomembrane, including:
[0038] (1) The bottom surface of the silo is flattened to ensure that there are no impurities within a vertical depth of 20 mm, and then the bottom surface is roughened to ensure that the depth of the roughness of the bottom surface is 3 mm;
[0039] (2) According to the reservoir bottom conditions, the geomembrane is cut into appropriate sizes and numbered for record. The exposed edges of the geomembrane are covered with sand bags;
[0040] (3) TPO geomembrane, new geomembrane and HDPE geomembrane were overlapped in sequence with a overlap width of 8 cm, and welded by a double-track automatic hot-melt welding machine at a welding temperature of 400°C and a welding speed of 2 m / min to fuse the edges of adjacent geomembranes;
[0041] (4) Mark the defects detected on the geomembrane and arrange for repairs until the retest is qualified;
[0042] The new geomembrane includes a substrate layer and an anti-slip layer coated on the lower surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-slip layer is 1:0.1;
[0043] The thickness ratio of TPO geomembrane, new geomembrane and HDPE geomembrane is 1:1:1;
[0044] The new geomembrane is prepared by the following method:
[0045] a. By weight, 30 parts of high-density polyethylene, 25 parts of low-density polyethylene, 20 parts of linear low-density polyethylene, 15 parts of polyethylene, 12 parts of ethylene-octene copolymer, 15 parts of polyetheretherketone, 10 parts of polycarbonate, 8 parts of modified polyester fiber, 7 parts of phenyl p-isopropyl salicylate, 6 parts of boron nitride and 1 part of antioxidant 1076 were placed in a twin-screw extruder at a main engine speed of 50 rpm, extruded through a die at 170° C., and calendered to obtain a substrate layer;
[0046] b. Dissolve 6 parts of thiophenyl-parathiocyanoacetone and 5 parts of isopropylthioxanthone in 10 parts of hexanediol diacrylate and 8 parts of tripropylene glycol diacrylate, and stir at 40° C. for 40 min. Then add 42 parts of aliphatic polyurethane acrylate, 15 parts of hyperbranched polyester acrylate, 15 parts of polypropylene frosting powder, 3 parts of siloxane polyether acrylate and 2 parts of fluorosilicone compound, continue stirring for 20 min, and after standing and stabilizing, obtain an anti-slip coating;
[0047] c. Applying the anti-slip coating on the lower surface of the substrate layer, pre-baking at 60°C for 30 seconds, and then aging at 40°C for 12 hours, thereby forming an anti-slip layer to obtain a new geomembrane;
[0048] In step a, the preparation method of the modified polyester fiber comprises the following steps:
[0049] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0050] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 1 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0051] S3. Stir and mix the silane coupling agent KH550 and 95% ethanol in a volume ratio of 1:400 at 40°C for 1 hour, then add FeCl3 to disperse evenly, and then add the preliminarily modified polyester fiber to soak for 1 hour. The weight of the silane coupling agent KH550 is 8% of the preliminarily modified polyester fiber. Take it out, wash it with water, and dry it to obtain the modified polyester fiber.
[0052] Example 2
[0053] A new type of double-track hot-melt welding process for geomembrane, including:
[0054] (1) The bottom surface of the silo is flattened to ensure that there are no impurities within a vertical depth of 22 mm, and then the bottom surface is roughened to ensure that the depth of the roughness of the bottom surface is 4 mm;
[0055] (2) According to the reservoir bottom conditions, the geomembrane is cut into appropriate sizes and numbered for record. The exposed edges of the geomembrane are covered with sand bags;
[0056] (3) TPO geomembrane, new geomembrane and HDPE geomembrane were overlapped in sequence with a lap width of 10 cm, and welded by a double-track automatic hot-melt welding machine at a welding temperature of 420°C and a welding speed of 2.2 m / min to fuse the edges of adjacent geomembranes;
[0057] (4) Mark the defects detected on the geomembrane and arrange for repairs until the retest is qualified;
[0058] The new geomembrane includes a substrate layer and an anti-slip layer coated on the lower surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-slip layer is 1:0.2;
[0059] The thickness ratio of TPO geomembrane, new geomembrane and HDPE geomembrane is 1.5:1:1.5;
[0060] The new geomembrane is prepared by the following method:
[0061] a. By weight, 38 parts of high-density polyethylene, 30 parts of low-density polyethylene, 24 parts of linear low-density polyethylene, 20 parts of polyethylene, 15 parts of ethylene-octene copolymer, 17 parts of polyetheretherketone, 13 parts of polycarbonate, 11 parts of modified polyester fiber, 10 parts of phenyl p-isopropyl salicylate, 8 parts of boron nitride and 2 parts of antioxidant 619 were placed in a twin-screw extruder at a main engine speed of 55 rpm, extruded through a die at 175° C., and calendered to obtain a substrate layer;
[0062] b. Dissolve 12 parts of thiophenyl-parathiocyanoacetone and 8 parts of isopropylthioxanthone in 20 parts of hexanediol diacrylate and 15 parts of tripropylene glycol diacrylate, and stir at 45° C. for 30 min. Then add 58 parts of aliphatic polyurethane acrylate, 23 parts of hyperbranched polyester acrylate, 20 parts of polypropylene frosting powder, 5 parts of silicone polyether acrylate and 3 parts of fluorosilicone compound, continue stirring for 30 min, and after standing and stabilizing, obtain an anti-slip coating;
[0063] c. Applying the anti-skid coating on the lower surface of the substrate layer, pre-baking at 65°C for 40 seconds, and then aging at 45°C for 18 hours, thereby forming an anti-skid layer to obtain a new geomembrane;
[0064] In step a, the preparation method of the modified polyester fiber comprises the following steps:
[0065] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0066] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 2 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0067] S3. Stir and mix the silane coupling agent KH560 and 95% ethanol in a volume ratio of 1:500 at 50°C for 2 hours, then add FeCl3 to disperse evenly, and then add the initially modified polyester fiber to soak for 2 hours. The weight of the silane coupling agent KH560 is 10% of the initially modified polyester fiber. Take it out, wash it with water, and dry it to obtain the modified polyester fiber.
[0068] Example 3
[0069] A new type of double-track hot-melt welding process for geomembrane, including:
[0070] (1) The bottom surface of the silo is flattened to ensure that there are no impurities within a vertical depth of 25 mm, and then the bottom surface is roughened to ensure that the depth of the roughness of the bottom surface is 5 mm;
[0071] (2) According to the reservoir bottom conditions, the geomembrane is cut into appropriate sizes and numbered for record. The exposed edges of the geomembrane are covered with sand bags;
[0072] (3) TPO geomembrane, new geomembrane and HDPE geomembrane were overlapped in sequence with staggered seams, with an overlap width of 12 cm, and welded by a double-track automatic hot-melt welding machine at a welding temperature of 450°C and a welding speed of 2.5 m / min to fuse the edges of adjacent geomembranes;
[0073] (4) Mark the defects detected on the geomembrane and arrange for repairs until the retest is qualified;
[0074] The new geomembrane includes a substrate layer and an anti-slip layer coated on the lower surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-slip layer is 1:0.3;
[0075] The thickness ratio of TPO geomembrane, new geomembrane and HDPE geomembrane is 2:1:1.8;
[0076] The new geomembrane is prepared by the following method:
[0077] a. By weight, 45 parts of high-density polyethylene, 32 parts of low-density polyethylene, 27 parts of linear low-density polyethylene, 25 parts of polyethylene, 18 parts of ethylene-octene copolymer, 20 parts of polyetheretherketone, 16 parts of polycarbonate, 13 parts of modified polyester fiber, 12 parts of phenyl p-isopropyl salicylate, 11 parts of boron nitride and 3 parts of antioxidant 703 were placed in a twin-screw extruder at a main engine speed of 60 rpm, extruded through a die at 180° C., and calendered to obtain a substrate layer;
[0078] b. Dissolve 15 parts of thiophenyl-parathiocyanoacetone and 10 parts of isopropylthioxanthone in 25 parts of hexanediol diacrylate and 20 parts of tripropylene glycol diacrylate, and stir at 50° C. for 20 min. Then add 70 parts of aliphatic polyurethane acrylate, 30 parts of hyperbranched polyester acrylate, 30 parts of polypropylene frosting powder, 7 parts of silicone polyether acrylate and 5 parts of fluorosilicone compound, continue stirring for 40 min, and after standing and stabilizing, obtain an anti-slip coating;
[0079] c. Applying the anti-slip coating on the lower surface of the substrate layer, pre-baking at 70°C for 50 seconds, and then aging at 50°C for 24 hours, thereby forming an anti-slip layer to obtain a new geomembrane;
[0080] In step a, the preparation method of the modified polyester fiber comprises the following steps:
[0081] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0082] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 3 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0083] S3. Stir and mix the silane coupling agent KH570 and 95% ethanol in a volume ratio of 1:600 at 60°C for 3 hours, then add FeCl3 to disperse evenly, and then add the preliminarily modified polyester fiber and soak for 3 hours. The weight of the silane coupling agent KH570 is 12% of the preliminarily modified polyester fiber. Take out, wash and dry to obtain the modified polyester fiber.
[0084] Example 4
[0085] The difference from Example 2 is that the thickness ratio of the substrate layer to the anti-slip layer is 1:0.5.
[0086] Example 5
[0087] The difference from Example 2 is that the thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is 3:1:2.5.
[0088] Example 6
[0089] The difference from Example 2 is that the modified polyester fiber is replaced by polyester fiber, and the preparation method of the modified polyester fiber is not disclosed.
[0090] Example 7
[0091] The difference from Example 2 is that the preparation method of the modified polyester fiber comprises the following steps:
[0092] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0093] S2. Stir and mix silane coupling agent KH560 and 95% ethanol at a volume ratio of 1:500 at 50°C for 2 hours, then add the pretreated polyester fiber and soak it for 2 hours. The weight of the silane coupling agent KH560 is 10% of the pretreated polyester fiber. Take it out, wash it with water, and dry it to obtain modified polyester fiber.
[0094] Example 8
[0095] The difference from Example 2 is that step c is:
[0096] The anti-skid layer coating is coated on the lower surface of the substrate layer and cured at 50° C. for 24 hours to form an anti-skid layer and obtain a new geomembrane.
[0097] Comparative Example 1
[0098] The difference from Example 2 is that the lower surface of the substrate layer is not coated with an anti-slip layer, and the preparation method of the novel geomembrane does not include step b and step c.
[0099] The new geomembranes in the above-mentioned Examples 1-8 and Comparative Examples 1-2 were subjected to performance tests. The tensile strength and elongation at break of different samples were tested according to CJ / T234-20066.6. The UV resistance of different samples was tested according to CJ / T234-20066.14. The retention of OIT at normal pressure after 1600 hours of ultraviolet irradiation was tested. The anti-seepage performance of different samples was tested according to CJ / T234-20066.16. Welded specimens with a size of 25 mm × 150 mm were cut, and the welded parts were subjected to tearing tests and shear tests using an Examo300F tensile testing machine. The peel strength and shear strength were both taken as the average values of the two seams. The results are shown in Table 1.
[0100] Table 1
[0101]
[0102] From the results in Table 1, it can be seen that the double-track hot-melt welding process of the new geomembrane of the present application enables the frosted surface of the new geomembrane to fit tightly with the rough surface of the reservoir bottom, and relative sliding is not likely to occur between the two, thereby extending the service life of the geomembrane and meeting the engineering anti-seepage requirements.
[0103] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A new type of double-track hot-melt welding process for geomembrane, characterized in that: include: (1) The bottom surface of the silo is flattened to ensure that there are no impurities within a vertical depth of 20-25 mm, and then the bottom surface is roughened to ensure that the depth of the roughness of the bottom surface is 3-5 mm; (2) According to the reservoir bottom conditions, the geomembrane is cut into appropriate sizes and numbered for record. The exposed edges of the geomembrane are covered with sand bags; (3) The TPO geomembrane, the new geomembrane and the HDPE geomembrane are overlapped in sequence and welded by a double-track automatic hot-melt welding machine to fuse the edges of the adjacent geomembranes; (4) Mark the defects detected on the geomembrane and arrange for repairs until the retest is qualified; The novel geomembrane comprises a substrate layer and an anti-slip layer coated on the lower surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-slip layer is 1:(0.1-0.3).
2. The double-track hot-melt welding process of the novel geomembrane according to claim 1 is characterized in that: In step (3), the welding temperature is 400-450°C and the welding speed is 2-2.5 m / min.
3. The double-track hot-melt welding process of the novel geomembrane according to claim 1 is characterized in that: In step (3), the overlap width is 8-12 cm.
4. The double-track hot-melt welding process of the novel geomembrane according to claim 1 is characterized in that: The thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is (1-2):1:(1-1.8).
5. The double-track hot-melt welding process of the novel geomembrane according to claim 1 is characterized in that: The novel geomembrane is prepared by the following method: a. By weight, 30-45 parts of high-density polyethylene, 25-32 parts of low-density polyethylene, 20-27 parts of linear low-density polyethylene, 15-25 parts of polyethylene, 12-18 parts of ethylene-octene copolymer, 15-20 parts of polyetheretherketone, 10-16 parts of polycarbonate, 8-13 parts of modified polyester fiber, 7-12 parts of phenyl p-isopropyl salicylate, 6-11 parts of boron nitride and 1-3 parts of antioxidant are placed in a twin-screw extruder, the main engine speed is 50-60rpm, and the extrusion die is extruded at 170-180°C and then calendered to obtain a substrate layer; b. Dissolve 6-15 parts of thiophenyl-parathiocyanoacetone and 5-10 parts of isopropylthioxanthone in 10-25 parts of hexanediol diacrylate and 8-20 parts of tripropylene glycol diacrylate, and stir at 40-50° C. for 20-40 minutes, then add 42-70 parts of aliphatic polyurethane acrylate, 15-30 parts of hyperbranched polyester acrylate, 15-30 parts of polypropylene frosting powder, 3-7 parts of silicone polyether acrylate and 2-5 parts of fluorine silicon compound, continue stirring for 20-40 minutes, and after standing and stabilizing, obtain an anti-slip coating; c. Apply the anti-skid coating on the lower surface of the substrate layer, pre-bake at 60-70°C for 30-50s, and then mature at 40-50°C for 12-24h to form an anti-skid layer and obtain a new geomembrane.
6. The double-track hot-melt welding process of the novel geomembrane according to claim 5 is characterized in that: In step a, the antioxidant is selected from at least one of antioxidant 1076, antioxidant 619, and antioxidant 703.
7. The double-track hot-melt welding process of the novel geomembrane according to claim 5 is characterized in that: In step a, the preparation method of the modified polyester fiber comprises the following steps: S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber; S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 1-3 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber; S3. Stir and mix silane coupling agent and ethanol in a volume ratio of 1:(400-600) at 40-60°C for 1-3h, then add FeCl3 to disperse evenly, then add the initially modified polyester fiber and soak for 1-3h, take out, wash with water, and dry to obtain the modified polyester fiber.
8. The double-track hot-melt welding process of the novel geomembrane according to claim 7 is characterized in that: The silane coupling agent is selected from at least one of KH550, KH560 and KH570.
9. The double-track hot-melt welding process of the novel geomembrane according to claim 7 is characterized in that: In step S3, the weight of the silane coupling agent is 8-12% of the initially modified polyester fiber.
10. The double-track hot-melt welding process of the novel geomembrane according to claim 1 is characterized in that: In step (1), the roughening treatment of the bottom surface of the reservoir includes one or more of chiseling, grinding, high-pressure jetting, and milling.
Citation Information
Cited By
Transition zone impermeable material as well as preparation method and application thereof
CN120209436A
A transition zone impermeable material, its preparation method and application
CN120209436B